Construction of management tools for early warning of prevacuum steam sterilization failure - Xin Zhao; Ting Liu; Ning Ma; Ran Wang; Ying Li; Tong Shen (PLoS ONE, 2025)
Objective The aim of this study is to develop a set of management tools for early warning of steam sterilization failure, including a failure risk checklist and a calculation model for assessing early sterilization failure risk, and to verify the early warning effectiveness of the management tools through check experiment. Methods This study included two stages. The first stage involved the construction of a failure risk checklist and the development of a computational formula for early sterilization failure risk by expert consultation. In the second stage, the early warning effectiveness of the sterilization failure management tools was verified through a comparative verification method based on the consultation results of two experts. Results The evaluation system comprised a total of 10 early warning indicators divided into 3 categories: "Staff", "Steam sterilizer" and "Medical devices". The Cronbach’s α coefficient for internal consistency reliability was 0.837, the total content validity index (S-CVI) was 0.884, and the item-content validity (I-CVI) ranged from 0.762 to 1. In management practices, the sterilization qualification rate of the experimental group was 100%, compared to 99.78% in the control group. There were significant differences between the two groups in terms of accidental downtime (hours) and the normal operation rate of the equipment caused by equipment failure. Conclusion This study constructed an early warning model for the vacuum steam sterilization process failures. This model facilitates more accurate identification of sterilization failure risks, which helps medical institutions in enhancing sterilization quality control and early interventions.